Relações de trabalho e produção na indústria da reciclagem: uma análise a partir da associação de catadores no município de Jaguari-RS - Lock, Andrea Pereira (2013)
In Brazil, the National Politics of Solid Wastes, established in August 2010, is considered a historic landmark in the environmental management in the country. Since from this politics, the counties need to adapt itself the new norms and are responsible by management of their wastes. The present work has the objective understand the labor and production relations between the Association of Collectors Profetas da Ecologia of Jaguari RS, the town government and the purchasers of recyclable materials, before the National Politics of Solids Wastes. The methodology suggested is the qualitative abordage and the case study with strategy of research using as investigation tool the documental research, the dialog, interviews and observation in the technical visits, meetings, and workshops. The social actors involved in the research are the recyclable wastes collectors associated, the Municipal Government across the Planning and Environment Secretary and the purchaser of recyclable materials. The research was executed on the period of 2009, with the formation of Association, until the beginning of 2013. The work and the production of ARPEJ are fundamental to the community, since it performs the selective collection in town, getting better rent and lower allocation of waste to sanitary embankment; besides, collaborates with the healthy environment, with the prefecture, decreasing costs to municipal coffers. Highlights that was there advance in the social relations of collectors with the town government and with the community of Jaguary RS. Understands that the recycling industry provides opportunities work and rent for a portion of a population and provides a alternative in the economy of natural resources. Conclude, that remains to be made to the National Politics of Solid Wastes is applied to tows, which requires envelopment of all community and management process by government agencies.